On the Faintly e-Continuous Functions - Caldas, Miguel (Sarajevo Journal of Mathematics, 2024)
A new class of functions, called faintly e-continuous functions, has been defined and studied. Relationships among faintly e- continuous functions and e-connected spaces, e-normal spaces and e-compact spaces are investigated. Furthermore, the relationships between faintly e-continuous functions and graphs are investigated. 2000 Mathematics Subject Classification. 54B05, 54C08, 54D10